2012
DOI: 10.1016/j.drudis.2011.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Understanding latent tuberculosis: the key to improved diagnostic and novel treatment strategies

Abstract: Treatment of latent tuberculosis (LTBI) is a vital component of tuberculosis elimination but is not efficiently implemented with available diagnostics and therapeutics. The tuberculin skin test and interferon gamma release assays can inform that infection has occurred but do not prove that it persists. Treatment of LTBI with isoniazid targets actively replicating bacilli but not non-replicating populations, prolonging treatment duration. Developing more predictive diagnostic tests and treatments of shorter dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 60 publications
4
81
0
Order By: Relevance
“…Isoniazid's main activity is bactericidal, highly effective against actively replicating bacteria (30, 31), but unlikely to completely cure a LTBI with few replicating bacteria (29). In vitro and mouse studies have shown that rifampicin and rifapentine can sterilize (31,32) and would therefore be expected to more often result in a cure of LTBI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isoniazid's main activity is bactericidal, highly effective against actively replicating bacteria (30, 31), but unlikely to completely cure a LTBI with few replicating bacteria (29). In vitro and mouse studies have shown that rifampicin and rifapentine can sterilize (31,32) and would therefore be expected to more often result in a cure of LTBI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that ART, perhaps through immune reconstitution, would increase the proportion of latent infections cured by isoniazid (7,29). A recent pragmatic randomized controlled trial in South Africa examined the additional impact of IPT in patients already receiving ART (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several recent evidences support the notion that LTBI is not a single defined state but comprises a heterogeneous and dynamic spectrum of interaction patterns between host and pathogen [8]. This heterogeneity may lead to different outcomes, ranging from clearing the infection to pre-reactivation of the disease, probably reflecting various states of bacterial behaviour between dormancy and steady state replication [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The WHO recommends systematic screening of contacts of TB patients and high-risk groups in order to achieve the post 2015 tuberculosis strategy aiming to reduce the tuberculosis incidence by 90% by 2035 compared with the 2015 incidence [6]. Improving diagnostic tools of LTBI is therefore urgently needed [7,8], and more research should be done to identify biomarkers able to predict the progression from LTBI to active TB disease.…”
Section: Introductionmentioning
confidence: 99%